1999
DOI: 10.1007/bf03345477
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and tolerability of slow release lanreotide treatment in active acromegaly

Abstract: This single-center open sequential study aimed at comparing the efficacy of a 6-month treatment with lanreotide (LAN) (60-90 mg/month i.m.), to that of octreotide (OCT) (0.3-0.6 mg/day s.c.) in 45 patients with active acromegaly (GH, 63.2+/-12.1 ng/ml, IGF-I, 757+/-67.1 ng/ml). After 6 months of OCT treatment, safe GH (fasting <2.5, glucose suppressed <1 ng/ml) and IGF-I (normalized for age) levels were achieved in 23 patients. After treatment withdrawal, GH levels significantly increased in all patients, thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
2
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 29 publications
4
37
2
1
Order By: Relevance
“…Although inadequate use of each drug may have allocated patients wrongly in the category of nonresponder, a difference in responsiveness to each drug seems a more likely explanation. In agreement with our observation, Colao et al (24) described recently 4 patients not normalized with octreotide but responding to lanreotide SR. Switching patients from one somatostatin analog to another might therefore occasionally be effective if patients are initially insuf®ciently controlled.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although inadequate use of each drug may have allocated patients wrongly in the category of nonresponder, a difference in responsiveness to each drug seems a more likely explanation. In agreement with our observation, Colao et al (24) described recently 4 patients not normalized with octreotide but responding to lanreotide SR. Switching patients from one somatostatin analog to another might therefore occasionally be effective if patients are initially insuf®ciently controlled.…”
Section: Discussionsupporting
confidence: 94%
“…Although not proven by a randomised double blind clinical trial, these data strongly suggest that both drugs are equally effective. Moreover, both on an anamestic base (22, our data) and in sequential therapy (24), subcutaneous octreotide and lanreotide SR have been found to be equally effective in the same patients. One study showed that subcutaneous octreotide was able to induce an earlier reduction in IGF-I levels and a more marked reduction in GH levels compared with lanreotide, but after six months of therapy the effect was similar with both drugs (26).…”
Section: Discussionmentioning
confidence: 53%
“…1,[12][13][14]22,46 Somatostatin analogs provide a more effective treatment option and can normalize IGF-I levels in 50 to 60% of patients. 3,8,9,11,24,36 The more recently introduced GH receptor antagonists appear to have encouraging prospects.…”
Section: Role Of Gks In Multimodal Therapymentioning
confidence: 99%
“…These data on lanreotide are in line with the demonstration that first-line SA therapy is able to improve clinical conditions and surgical outcome (15,16), induce a better biochemical disease control, and reduce the duration of hospitalization after surgery and the prevalence of secondary hypopituitarism (32). As shown in Table 2, previous studies have shown that octreotide long-acting release (LAR) and lanreotide, both as slow-release (SR) and ATG formulations, are very effective in inducing hormone control and tumor shrinkage in acromegalic patients, reporting a reduction in tumor mass rate of 31.1-82% (7,8,(17)(18)(19)(20)(21)(22)(23)(24)(25). Particularly, in the review by Bevan et al (8), tumor shrinkage was found in 51% of patients receiving SA as first-line treatment and in 27% of patients treated after unsuccessful surgery and/or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%